A systematic study of the cellular metabolic regulation of Jhdm1b in tumor cells1. Issue 7 (16th July 2015) - Yu, Xi; Wang, Jiaxu; Wu, Jihui; Shi, Yunyu
<x xml:space="preserve">Abstract</x> Jhdm1b knockdown cells enhanced glutaminolysis to maintain the Krebs cycle by upregulating RIP3 expression.